Who Refers Whom? The Effects of Teacher Characteristics on Disciplinary Office Referrals - Michael S. Hayes; Jing Liu; Seth Gershenson (Institute of Labor Economics (IZA), 2022)
Teachers affect a wide range of students' educational and social outcomes, but how they contribute to students' involvement in school discipline is less understood. We estimate the impact of teacher demographics and other observed qualifications on students' likelihood of receiving a disciplinary referral. Using data that track all disciplinary referrals and the identity of both the referred and referring individuals from a large and diverse urban school district in California, we find students are about 0.2 to 0.5 percentage points (7% to 18%) less likely to receive a disciplinary referral from teachers of the same race or gender than from teachers of different demographic backgrounds. Students are also less likely to be referred by more experienced teachers and by teachers who hold either an English language learners or special education credential. These results are mostly driven by referrals for defiance and violence infractions, Black and Hispanic male students, and middle school students. While it is unclear whether these findings are due to variation in teachers' effects on actual student behavior, variation in teachers' proclivities to make disciplinary referrals, or a combination of the two, these results nonetheless suggest that teachers play a central role in the prevalence of, and inequities in, office referrals and subsequent student discipline.
Keywords: I2; J7; 330; exclusionary discipline; teacher effectiveness; office referrals